2017
DOI: 10.1021/acs.joc.6b03052
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Synthesis and Biological Evaluation of C1-Epimeric and Desmethyl Monomeric Nuphar Analogues

Abstract: A class of monomeric nuphar analogues that are either epimeric at C1 and C1' or lack the naturally occurring methyl group at those positions were synthesized and evaluated for biological activity. The syntheses feature enantioselective vinylogous Mukaiyama-Mannich (vM-Mannich) reactions catalyzed by chiral phosphoric acids that proceed with excellent diastereoselectivity. Biological assays reveal that both the desmethyl and C1-epimeric monomeric nuphar analogous are able to induce rapid apoptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 39 publications
(80 reference statements)
0
6
0
Order By: Relevance
“…Phlorotannins possessed therapeutic properties [85][86][87]. Phlorotannins are specifically present as the only group of phenolic compounds in brown algae.…”
Section: Phaeophyceaementioning
confidence: 99%
“…Phlorotannins possessed therapeutic properties [85][86][87]. Phlorotannins are specifically present as the only group of phenolic compounds in brown algae.…”
Section: Phaeophyceaementioning
confidence: 99%
“…Oxoesters 1a,b have also been employed in three-component vinylogous Mannich (VM) reactions as the electrophilic acceptors upon reaction with an aromatic amine followed by several steps to obtain the indolizidine and quinolizidine frameworks with very high enantio-and diastereoselectivity (Scheme 1, eq. a) [15][16][17]. To the best of our knowledge, we are aware of only one example featuring a Mannich reaction of oxoesters 1a,b, in which these compounds behave as nucleophilic donor.…”
Section: Alkylmentioning
confidence: 99%
“…Recently, synthetic studies of nuphar alkaloids, including unnatural-type alkaloids, have been reported, [30][31][32][33][34][35][36] and several of these studies are aimed at developing new anti-cancer agents. Despite the unique stereostructures of dimeric sesquiterpene thioalkaloids have been determined in the 1970s, their total synthesis was not completed until 2013 by Jansen and Shenvi 30) and Korotkov et al in 2015.…”
Section: Synthesis Of Nuphar Alkaloids and Their Development As Anti-cancer Agentsmentioning
confidence: 99%